Evaluation of mRNA expression of the transcription factors of Th1 and Th2 subsets (T-bet and GATA-3) in periodontal health and disease - A pilot study in south Indian population - Nichenametla Rajesh; Kurumathur Vasudevan Arun; Tirumelveli Saravanan Subbu Kumar; Kondareddy Krishna Mohan Reddy; Swarna Alamelu; Bhimavarapu Ravinder Reddy (Wolters Kluwer Medknow Publications, 2015)
Background: Based on their respective pro- or anti-inflammatory cytokine profiles, the Th1/Th2 paradigm explains pathogenic mechanisms involved in periodontal disease. Establishment of Th1 and Th2 subsets from a naive T-cell precursor depends on transcriptional regulation. The aim of this study was to compare the expression of master transcription factor regulators T-bet and GATA-3, respectively, to indicate the predominance of Th1 and Th2 subsets in the presence and absence of periodontal disease. Materials and Methods: A gingival tissue biopsy sample was obtained from each of 10 severe periodontitis patients (>5 mm attachment loss) and 10 periodontally healthy patients (no attachment loss). Biopsies were immediately processed by real-time reverse transcriptase polymerase chain reaction and the difference in mRNA expression of T-bet and GATA-3 was assessed for each group. Results: The mRNA expression of T-bet was marginally increased about 1.31-fold in disease, while the GATA-3 levels showed a significant decrease of 4.39-fold in disease. Conclusion: The advanced periodontal lesions lack Th2 cells, which produce anti-inflammatory cytokines. The biopsies were therefore dominated by Th1 cells, which activate macrophages and osteoclasts.